2008
DOI: 10.1111/j.1365-2893.2007.00965.x
|View full text |Cite
|
Sign up to set email alerts
|

MBL2 and MASP2 gene polymorphisms in patients with hepatocellular carcinoma

Abstract: The pathogenesis of hepatocellular carcinoma (HCC) is not fully understood, but the majority of patients with HCC are associated with hepatitis B virus (HBV) or hepatitis C virus (HCV) infection. Mannan-binding lectin (MBL) is a collectin that can act directly as opsonine or activate MBL-associated serine proteases (MASPs) thus initiating the antibody-independent pathway of the complement system. In our study, we analysed two MBL2 and MASP2 functional polymorphisms (MBL2 allele A/0 and MASP2 D120G) as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…This study performed analysis in subjects divide into 4 groups in accordance with infection status of hepatitis B and C, and found no significant association in all groups6. We considered that the insignificant result was due to limited sample size and the study design further diminished the statistical power.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This study performed analysis in subjects divide into 4 groups in accordance with infection status of hepatitis B and C, and found no significant association in all groups6. We considered that the insignificant result was due to limited sample size and the study design further diminished the statistical power.…”
Section: Discussionmentioning
confidence: 89%
“…The above mentioned variants and its haplotypes are capable of effecting the serum MBL2 level significantly, and maintaining appropriate level of MBL2 is of critical importance in combating infection for human body. So far seldom studies on the association between MBL2 polymorphisms and HCC risk were reported, only a study conducted in Italian population found no significant association between MBL2 genotypes and HCC risk6, however, the study has limited sample size, and it performed stratification according to both hepatitis B and C infection, which led to reduction in both sample size and statistical power. Therefore, in order to reveal the association in MBL2 polymorphisms and HCC risk, we have conducted a case-control study in southeast China.…”
mentioning
confidence: 99%
“…Moreover, it was reported that the mbl 2 polymorphisms may be an important factor in determining the prognosis in patients with hepatitis B virus infection [13]. However, the data from several studies argue against a role of MBL in chronicity and progression of HBV [9,17]. For reason given above, a meta-analysis in a large population was fulfilled in present study.…”
Section: Introductionmentioning
confidence: 82%
“…It was concluded that MBL would not appear to be involved significantly in host susceptibility to CHB, but might play an important role in exacerbation and progression of hepatitis B. These genotypes (AO/OO) might be associated with the natural wound healing process, which may develop the necroinflammation, rather than carcinogenesis [16,17]. …”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only few studies regarding the prevalence of the p.D371Y polymorphism are available so far. In a control group of 164 Italian healthy subjects (Segat et al. , 2008), the frequencies of MASP2 p.D371Y were C/C = 0.06, A/C = 0.27 and A/A = 0.67, with MAF = 0.20 (Segat et al.…”
Section: Discussionmentioning
confidence: 99%